Engineering characteristics of cement modified base course material for Western Australian pavements - Jitsangiam, Peerapong; Chummuneerat, Suphat; Nikraz, Hamid (Engineers Media Pty Ltd, 2013)
In North America, cement-modified soil (CMS) is described as a soil that has been treated with a relatively small amount of cement in order to improve its engineering properties and make it suitable for construction purposes. CMS leads to a typical soil stabilisation technique employed in Western Australian base course material: hydrated cement treated crushed rock base (HCTCRB), which incorporates an additional hydration process which differs from the original CMS technique. However, because the HCTCRB technique was developed mainly by an empirical approach based on pavement trials, it is posited that HCTCRB itself may be inconsistent with regard to fundamentals such as quality control and uniformity of elements. This then causes uncertainty during the application of HCTCRB with regard to its essential qualities, mix proportion, mixing and curing processes, and construction processes. The effects of these ambiguities need to be better understood in order to maximise the application of this material to new pavement design methods where reliability and consistency is crucial.This study aimed to comprehensively investigate the effects on HCTRB of the amounts of mixing water added, hydration period, and compaction effort on physical properties (ie. gradation and surface properties), and mechanical properties (ie. shear strength parameters, resilient modulus and permanent deformation) using scanning electron microscopy (SEM), conventional triaxial tests and repeated load triaxial tests. HCTCRB demonstrates superior performance to the original material in terms of resilient modulus and permanent deformation. SEM and static triaxial tests revealed that crushed rock base shows higher internal friction angles but less cohesion than HCTCRB. The hydration period of HCTCRB during the manufacturing process was found to have an insignificant effect on particle size distribution. However, hydration period does affect the permanent deformation and resilient modulus characteristics of HCTCRB.